2017
DOI: 10.1103/physrevlett.118.133904
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Photon Production in Time-Dependent Epsilon-Near-Zero Materials

Abstract: Quantum field theory predicts that a spatially homogeneous but temporally varying medium will excite photon pairs out of the vacuum state. However, this important theoretical prediction lacks experimental verification due to the difficulty in attaining the required nonadiabatic and large amplitude changes in the medium. Recent work has shown that in epsilon-near-zero (ENZ) materials it is possible to optically induce changes of the refractive index of the order of unity, in femtosecond time scales. By studying… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
(90 reference statements)
0
35
0
Order By: Relevance
“…modulated, and if the temporal phase change is uniform over the pulse duration, the optical spectrum can be rigidly shifted. This effect can be interpreted as time-refraction [1,2], a phenomenon that attracted the attention of the research community owing to its link with the dynamical Casimir effect and Hawking radiation, and its implication in the formation of temporal band-gap structures and non reciprocal devices [3][4][5][6][7][8]. Strong enhancement of light-matter interaction has been observed in the spectral region where the real part of the dielectric permittivity ( [ε r ]) of a medium approaches zero (ENZ) [9][10][11].…”
mentioning
confidence: 99%
“…modulated, and if the temporal phase change is uniform over the pulse duration, the optical spectrum can be rigidly shifted. This effect can be interpreted as time-refraction [1,2], a phenomenon that attracted the attention of the research community owing to its link with the dynamical Casimir effect and Hawking radiation, and its implication in the formation of temporal band-gap structures and non reciprocal devices [3][4][5][6][7][8]. Strong enhancement of light-matter interaction has been observed in the spectral region where the real part of the dielectric permittivity ( [ε r ]) of a medium approaches zero (ENZ) [9][10][11].…”
mentioning
confidence: 99%
“…Another experiment that relies on this mechanism is described in [7], where the refractive index of a thinfilm epsilon-near-zero metamaterial is changed rapidly in time, building on experiments performed in [62,68]. In light of the present results, additional physics can be expected associated with the linear frequency mixing mechanisms.…”
Section: Discussionmentioning
confidence: 63%
“…In most experimental scenarios however, the simple plane waves are not accessible, and are instead replaced by structured paraxial beams. Let us once again consider a homogeneous bulk medium where W º W ( ) x i i 2 2 , but where we restrict equation (7) to the paraxial limit, with the z-direction chosen to be the propagation direction.…”
Section: Paraxial Wavesmentioning
confidence: 99%
“…As the wavelength in an ENZ material is extremely long, the phase of the eigenmode is almost constant, allowing, for example, wavefront shaping [7] for imaging applications. Another interesting feature of the ENZ materials is pronounced enhancement of nonlinearities [8,9]. It was reported that ENZ can also facilitate control over emission and interaction of quantum emitters (QE) [10] embedded in an ENZ cavity, and that emitted photons could hold substantial entanglement over large distances.…”
mentioning
confidence: 99%